La Teoría del Diseño Inteligente : un análisis desde el tomismo - Pavez, Juan Eduardo Carreño (Sapientia, 2011)
Michael Behe and William Dembski are two leaders of the Intelligent Design Theory, a proposal that emerges in response to anti-evolutionary and anti-finalistic models prevalent in certain academic and intellectual environments of the Anglo Saxon world. Behe speculation rests on the concept of “irreducible complex system”, understood as an ordered set of parts whose functionality is strictly dependent on its structural indemnity, and its origin is therefore refractory to gradualist explanations. These systems, according to Behe, are present in living beings, allowing the inference that they are not the product of blind and random mechanisms, but the result of a design. Dembski, meanwhile, has addressed the problem from a quantitative perspective, developing a probabilistic algorithm known as “the explanatory filter”; according to the author, this filter allows to scientifically infer the presence of a design, both in artificial and natural entities. Beyond the neo- Darwinist criticism, we examine the proposal of these authors from the philosophical foundations of the Thomistic school. In our view, there are some valuable intuitions in the work of Behe and Dembski, yet often go unrecognized by the lack of formality in which they come forward, and the artefactual and mechanistic approach that both authors exhibit. This article focuses precisely on the explicitation of such intuitions.